Social innovation and social policy : theory, policy and practice - Baglioni, Simone; Sinclair, Stephen P. (Policy Press shorts. Research., 2018)
Social innovation has become a prominent theme in discussions of social policy reform across the world. This book examines why social innovation is important to social policy analysis. It discusses the theoretical and policy context of this concept; its origin and background; why it has emerged to prominence in recent years and how it has been applied. The book relates social innovation to key debates and issues in social policy. These include competing agency and structural explanations of and solutions to social problems; the relative efficacy of government and civil society initiatives; and the capacity of community and/or service user-led responses to address social problems. The book will be a valuable resource for a wide, international readership including social and public policy analysts, policy makers, practitioners and students.